Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 31



Work Step by Step

RECALL: $(F+G)(x) = F(x) + G(x)$ Using the formula above gives: $(F+F)(x) \\= F(x)+F(x) \\=(x^2-2)+(x^2-2) \\=2(x^2-2) \\=2(x^2)+2(-2) \\=2x^2-4$ To find $(F+F)(1)$, substitute $1$ to $x$ in the equation above to obtain: $(F+F)(x) = 2x^2-4 \\(F+F)(1) = 2(1^2)-4 \\(F+F)(1)=2(1)-4 \\(F+F)(1)=2-4 \\(F+F)(1)=-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.